Perencanaan Kampanye Public Relations â€œMari Bersatu Permata Bundaâ€ Untuk Meningkatkan Awareness Masyarakat Sekitar Terhadap Sekolah TK-SD-SMP Permata Bunda - Kesaulya, Charlene Mabelle Reina Ulyanti; Soewarso, Kiki (Jurnal Komunikasi Profesional, 2019)
Education is a very important thing that should be engaged by every individual, because it is related to the progress and development of a country. In this era of globalization, technology is growing very rapidly that has an impact in education. Schools should be able to adapt to the community and the surrounding environment. TK-SD-SMP Permata Bunda / Sekolah Permata Bunda is a public school operating under the Yayasan Permata Bunda which until now has no public relations role. Thus, it takes the role of public relations in designing more current programs to help schools in raising awareness of certain communities. The purpose of this non-thesis paper is to raise public awareness by using the nine steps of public relations strategy. The Campaign Mari Bersatu Permata Bunda is to let the public to know and understand that the school wants to invite students to not distinguish against one another, nor discriminate, and be united for the students to become better people in the future, and have good relationship with all alumni of Permata Bunda School. It is expected that this non-thesis paper can be adopted by various parties in running external communication strategies.Â Keywords: Public Awareness, External Communication Program, Mari Bersatu Permata Bunda Campaign, Public Relations in Educational Institutions